2018
DOI: 10.1177/0269215518808051
|View full text |Cite
|
Sign up to set email alerts
|

An economic evaluation of the SUNBEAM programme: a falls-prevention randomized controlled trial in residential aged care

Abstract: Objective: To estimate the cost-effectiveness of a strength and balance exercise programme (SUNBEAM) which has been shown to be clinically effective in reducing the rate of falls in residents of aged care facilities. Design: An economic evaluation was conducted alongside a pragmatic cluster randomized controlled trial that included 16 residential care facilities and 221 participants. Mean participant age was 86 years, 65% were female and 78% relied on a mobility aide. A cost-effectiveness analysis examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…These studies originated from Canada (n = 3), United States (n = 2), United Kingdom (n = 2), Australia (n = 2) and the Netherlands (n = 2), along with one study each from Spain and Germany. The study topics represented a wide range of QI strategies such as pharmacist-led medication reviews [16][17][18][19], peer coaching for safe resident handling [20][21], preventive practices for reducing falls [22][23], preventing pressure ulcers [24][25][26], infection prevention [27][28], and dealing with challenging behaviors [29][30]. Several studies involved a multidisciplinary team, comprised of geriatricians, pharmacists, psychologists, registered nurses, licensed practical nurses, recreational therapists and care-aides working in the LTC settings.…”
Section: Summary Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies originated from Canada (n = 3), United States (n = 2), United Kingdom (n = 2), Australia (n = 2) and the Netherlands (n = 2), along with one study each from Spain and Germany. The study topics represented a wide range of QI strategies such as pharmacist-led medication reviews [16][17][18][19], peer coaching for safe resident handling [20][21], preventive practices for reducing falls [22][23], preventing pressure ulcers [24][25][26], infection prevention [27][28], and dealing with challenging behaviors [29][30]. Several studies involved a multidisciplinary team, comprised of geriatricians, pharmacists, psychologists, registered nurses, licensed practical nurses, recreational therapists and care-aides working in the LTC settings.…”
Section: Summary Of the Included Studiesmentioning
confidence: 99%
“…Studies originating from Canada used a discounting rate of 3 to 5% [21,24,26], as compared to 7% in other studies originating from the United States [20], and Germany [23]. The uncertainties in the model input parameters of costs and outcome were addressed by one-way deterministic sensitivity analysis [18,[20][21][22]26,28], nonparametric bootstrapping [17], and probabilistic sensitivity analysis [16,[23][24][25]. Only two studies reported on a budget impact analysis [23,26].…”
Section: Summary Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations